Apakah Curah Hujan Berpengaruh terhadap Kejadian Demam Berdarah Dengue? - Cindy Lois Rompis; Oksfriani Jufri Sumampouw; Woodford Baren Joseph (Universitas Sam Ratulangi, 2020)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus transmitted through the bite of the Aedes aegypti mosquito. Environmental factors, such as rainfall, temperature and altitude influence the spread of DHF. This study aims to determine the correlation of rainfall with the incidence of DHF in Tomohon City in 2015-2017. This type of research uses correlational quantitative research using Time Series data. The study population was DHF sufferers who were recoded at the Tomohon City Health Office in 2015-2017. The sample of this reseach is the total population. Data were analyzed using Microsoft Excel and SPSS. Data is displayed in graph and table form. The correlation test results between rainfall and the incidence of DHF in Tomohon City obtained p = 0.019 which means the value of p <0.05. The conclusion of this study is that there is a relation between rainfall and the incidence of DHF in Tomohon City in 2015-2017.